Impact of the MIF -173G/C variant on cardiovascular disease risk: a meta-analysis of 9,047 participants - Fouda, Hamas; Ibrahim, Wisam N.; Shi, Zumin; Alahmadi, Fahad; Almohammadi, Yousef; Al-Haidose, Amal; Abdallah, Atiyeh M. (Frontiers in Cardiovascular Medicine, 2024)
Many factors contribute to the risk of cardiovascular disease (CVD), an umbrella term for several different heart diseases, including inflammation. Macrophage migration inhibitory factor (MIF) is an important immune modulator that has been shown to be involved in the pathogenesis of different heart diseases, so understanding pathogenic variants of the MIF gene is important for risk stratification. We therefore conducted a meta-analysis to investigate whether the MIF -173G/C (rs755622) polymorphism is associated with CVD. The PubMed, Science Direct, and Embase databases were searched from inception to June 2023 for case-control studies of the MIF -173G/C polymorphism and its relationship to any type of CVD. Correlations between the MIF -173G/C polymorphism and CVD were estimated by pooling the odds ratios (ORs) with 95% confidence intervals in allelic, dominant, and recessive models using random-effects meta-analysis. A total of 9,047 participants (4141 CVD cases and 4906 healthy controls) from 11 relevant studies were included. In the total population, there was no significant association between the MIF -173G/C (rs755622) polymorphism and the risk of developing CVD in the three different models. In a stratified analysis by ethnicity, the allelic model (C vs G) was significantly associated with CVD in the Arab and Asian populations (OR = 0.56, CI 0.42-0.75 and OR = 1.28, CI 1.12-1.46, respectively); the dominant model (CC+CG vs GG) was significantly associated with CVD in the Arab population (OR = 0.42, CI 0.30-0.61); while the recessive model (GG+GC vs CC) was associated with CVD susceptibility in the Arab population (OR = 3.84, CI 1.57-9.41). There were no significant associations between the MIF -173 G/C polymorphism and CVD risk in the European population. In conclusion, the MIF -173G/C polymorphism is associated with CVD in some populations.